2012
DOI: 10.1590/s0104-530x2012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Medição de desempenho em cadeias de suprimentos: um estudo na indústria automobilística

Abstract: Resumo: Muito da base conceitual sobre medição de desempenho nas empresas industriais foi construído sob a perspectiva interna, ou seja, empresas tratadas individualmente. Com o advento e expansão do conceito de gestão da cadeia de suprimentos, cresceu a demanda por uma revisão do conhecimento e dos sistemas de medição à luz da cadeia como um todo. Por sua vez, a introdução dos novos arranjos produtivos na indústria automobilística, como os condomínios industriais, estimulou o desenvolvimento de novos padrões … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…Performance measurement systems are a supporting element in the management of the supply chain of organizations, providing information to support decision-making [58].…”
Section: Performance Measurement Systems and Their Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…Performance measurement systems are a supporting element in the management of the supply chain of organizations, providing information to support decision-making [58].…”
Section: Performance Measurement Systems and Their Maturitymentioning
confidence: 99%
“…The conceptual basis for performance measurement systems is applied to the "organizational" approach. However, there is a need for review and adequacy of this knowledge already built for the supply chain management area [58].…”
Section: Performance Measurement Systems and Their Maturitymentioning
confidence: 99%
“…Regarding the investigations on the performance in supply chains, we cite a study by Greene t al. (2008), which investigated the influence of logistics processes in the SC strategy, resulting in a better performance in a global context, as well as a study by Sacomano & Pires (2012), which reported how performance measures upstream from the chain are strongly related to aspects such as quality, production, and quality of deliveries, while measures downstream from the chain have strategic and marketing character.…”
Section: Theoretical Reference and Hypothesesmentioning
confidence: 99%
“…This analysis is especially true in the during-phase disruption, while companies have to maintain their operations to fulfill customers' requirement. Nevertheless, authors (Chan, 2003;Cho et al, 2012;Sacomano Neto & Pires, 2012) emphasize that customer satisfaction is a result of the management of other KPIs. Due to this, customer satisfaction is the KPI that showed more connections to the elements of resilience.…”
Section: Critical Analysis Of the Findingsmentioning
confidence: 99%